Keseimbangan Psikologis Karyawan Kontrak Wanita: Studi tentang Stres Kerja dan Dukungan Organisasi - Lestari, Eva; Aprilia, Nugraini (DINASTI RESEARCH, 2025)
Male employees have higher psychological well-being than female employees, indicating that men feel more likely to achieve well-being in the workplace than women. The purpose of this study was to determine the relationship between work stress and perceived organizational support on the psychological well-being of female contract employees. This study used a quantitative method with 75 female respondents who were female contract employees in Kudus Regency. The research sample was obtained through non-probability in addition to purposive sampling. This study used a scale of psychological well-being, work stress, and perceived organizational support. The results of the two predictor regression analysis showed that there was a relationship between work stress and perceived organizational support on psychological well-being, with rx1.2y = 0.589 and a significance level of 0.000 (p <0.01), there was an effective contribution of 34.7%.